1971
DOI: 10.1098/rspb.1971.0006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adhesion in the rabbit abdominal aorta following the removal of the endothelium: a scanning and transmission electron microscopical study

Abstract: The initial reactions of the blood components and the intima of the rabbit abdominal aorta have been observed following mechanical trauma. The endothelium was removed by the insertion of a roughened metal probe into the lumen of the vessel, thus exposing the sub-endothelial fibres and the internal elastio lamina. On restoration of the blood flow, platelets and later leucocytes adhered to the injured surface. Only small clumps of platelets or single cells adhered to the surface. Under these conditions it was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1972
1972
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The release of ADP or some other platelet aggregation activators from damaged endothelial cells or smooth muscle cells of the media has also been suggested as a possible mechanism for platelet adhesion at injured sites in blood vessels [Honour and Mitchell, 1964;Born, 1966;Sheppard and French, 1971;Honour, Pickering and Sheppard, 1971]. In the present experiments exogenous ADP aggregated ASA treated platelets in vitro both with and without collagen, although in the presence of collagen, aggregation did not occur around the collagen fibres.…”
Section: Results (A) Injury To the Abdominal Aortamentioning
confidence: 45%
See 4 more Smart Citations
“…The release of ADP or some other platelet aggregation activators from damaged endothelial cells or smooth muscle cells of the media has also been suggested as a possible mechanism for platelet adhesion at injured sites in blood vessels [Honour and Mitchell, 1964;Born, 1966;Sheppard and French, 1971;Honour, Pickering and Sheppard, 1971]. In the present experiments exogenous ADP aggregated ASA treated platelets in vitro both with and without collagen, although in the presence of collagen, aggregation did not occur around the collagen fibres.…”
Section: Results (A) Injury To the Abdominal Aortamentioning
confidence: 45%
“…In this case more than endothelial removal was involved as damage occurred to the media. It has been shown that injury to the media, rather than just removal of endothelium, produces larger aggregates of platelets even in such areas which do not encourage gross thrombus formation [Sheppard and French, 1971]. As only endothelium was removed in the present experiments the platelets were probably adhering to subendothelial structures other than collagen and release of aggregation activators from the media was probably not involved.…”
Section: Results (A) Injury To the Abdominal Aortamentioning
confidence: 57%
See 3 more Smart Citations